A Reappraisal of Ventilatory Thresholds in Wheelchair Athletes With a Spinal Cord Injury: Do They Really Exist? - Baumgart, Julia Kathrin; Ettema, Gertjan; Griggs, Katy E.; Goosey-Tolfrey, Victoria Louise; Leicht, Christof Andreas (Frontiers in Physiology, 2021)
The ventilatory threshold (VT) separates low- from moderate-intensity exercise, the respiratory compensation point(RCP) moderate- from high-intensity exercise. Both concepts assume breakpoints in respiratory data. However, the objective determination of the VT and RCP using breakpoint models during upper-body modality exercise in wheelchair athletes with spinal cord injury has received little attention. Therefore, the aim of this study was to compare the fit of breakpoint models (i.e., two linear regression lines) with continuous no-breakpoint models (i.e., exponential curve/ 2nd order polynomial) to respiratory data obtained during a graded wheelchair exercise test to exhaustion. These fits were compared employing adjusted R2, and blocked bootstrapping was used to derive estimates of a median and 95% confidence intervals (CI). V̇O2-V̇CO2 and V̇E/V̇O2-time data were assessed for the determination of the VT, and V̇CO2-V̇E and V̇E/V̇CO2-time data for the determination of the RCP. Data of 9 wheelchair athletes with tetraplegia and 8 with paraplegia were evaluated. On an overall group-level, there was an overlap in the adjusted R2 median ± 95% CI between the breakpoint and the no-breakpoint models for determining the VT (V̇O2-V̇CO2: 0.991±0.003 vs 0.990±0.003; V̇E/V̇O2-time: 0.792±0.1019 vs 0.782±0.104, respectively) and RCP (V̇E-V̇CO2: 0.984±0.004 vs 0.984±0.004; V̇E/V̇CO2-time: 0.729±0.064 vs 0.691±0.063, respectively), indicating similar model fit. We offer two lines of reasoning: 1) breakpoints in these respiratory data exist but are too subtle to result in a significant difference in adjusted R2 between the investigated breakpoint and no-breakpoint models; 2) breakpoints do not exist, as has been argued previously. respectively) and RCT (V̇E/V̇CO2: 0.968±0.011 vs 0.967±0.011; V̇CO2-V̇E: 0.393±0.114 vs 0.408±0.111, respectively), indicating similar model fit. We offer two lines of reasoning: 1) breakpoints in these respiratory data exist, but are too subtle to result in a significant difference in adjusted R2 between the investigated breakpoint and no-breakpoint models; 2) breakpoints do not exist, as has been argued previously.